STRUKTUR TARI DULANG PADA MASYARAKAT MELAYU DI KECAMATAN STABAT, KABUPATEN LANGKAT - DEA HALIM (Gesture: Jurnal Seni Tari, 2014)
THE STRUCTURE OF THE MALAY SOCIETY PAN DANCE IN DISTRICT OF LANGKAT REGENCY STABAT Other dance was one of the traditional Malay tribes dance movement is the combination of motion of silat. This study aims to shed light on the existing structure at a smaller dance. To address the above research purposes, use the theories related to research topics, such as the notion of sejarahasal origin, structure and understanding. Data analysis in this study uses qualitative data collection techniques, deskritif done with observation, interviews, literature studies, and documentation. Time study conducted to discuss Pan dance for 3 months, i.e. from 4 June 2014 until end of August 2014. The location of the research is the coastal village of Gemi, district of Langkat Regency Stabat. Based on the research that has been done, no one knowing when, where, and who created the dance of Pan. The dance is named after Pan because it uses a smaller property. Pan is a usually-lipped talam compatriots on the edges and footed. Pan is a welcoming dance dance as well as a tribute to the who held an event and serve as dance entertainment. In motion dance Pan, the majority of the movement is derived from the gerakjurus silat. Pan just dance performed by a group of male dancers and odd. The dance has a structure and a smaller structure in which can be explained through the description of the range of motion within a smaller dance. Pan remains dance performed in. Keywords: Dance, Dance Structur